Adopting TMR for physician/nurse use. - Hammond, W. E. (American Medical Informatics Association, 1991)
A major problem which must be overcome before on-line medical records become widely accepted and used is the interface between the human and the computer. This paper presents the evolution of an interface, over time, which recognizes and addresses important characteristics a system must exhibit to encourage human acceptance. Areas discussed include data entry, displays, and function and parameter specifications.